Hadith #776 - Sahih Muslim - Mutarrif bin 'Abdullah (Sahih Muslim)
I and ‘Imran b. Husain said prayer behind ‘Ali b. Abu, Talib. He recited takbir when he prostrated, and he recited takbir when he raised his head and he recited takbir while rising up (from the sitting position at the end of two rak’ahs). When we had finished our prayer, ‘Imran caught hold of my hand and said: He (Hadrat Ali) has led prayer like Muhammad (ﷺ) or he said: He in fact recalled to my mind the prayer of Muhammad (may peace be upon him.)
Grade: Sahih

Hadith #2855 - Sahih Muslim - Mutarrif bin 'Abdullah (Sahih Muslim)
‘Imran b. Husain said to me: Should I not narrate to you a hadith today by which Allah will benefit you subsequently-and bear in mind that Allah’s Messenger (ﷺ) made some members of his family perform ‘Umra within ten days of Dhu’l-Hijja. No verse was revealed to abrogate that, and he (the Holy Prophet) did not refrain from doing it till he died. So after him everyone said as he liked, (but it would be his. personal opinion and not the verdict of the Shari’ah).
Grade: Sahih

Hadith #2859 - Sahih Muslim - Mutarrif bin 'Abdullah (Sahih Muslim)
‘Imran b. Husain sent for me during his illness of which he died, and said: I am narrating to you some ahadith which may benefit you after me. If I live you conceal (the fact that these have been transmitted by me), and if I die, then you narrate them if you like (and these are): I am blessed, and bear in mind that the Messenger of Allah (ﷺ) combined Hajj and Umra. Then no verse was revealed in regard to it in the Book of Allah (which abrogated it) and the Messenger of Allah (ﷺ) did not fo
Grade: Sahih

Hadith #7236 - Sahih Muslim - Mutarrif bin 'Abdullah (Sahih Muslim)
I came to Allah’s Apostle (ﷺ) as he was reciting:” Abundance diverts you” (cii. 1). He said: The son of Adam claims: My wealth, my wealth. And he (the Holy Prophet) said: O son of Adam. is there anything as your belonging except that which you consumed, which you utilised, or which you wore and then it was worn out or you gave as charity and sent it forward?
Grade: Sahih

Hadith #7237 - Sahih Muslim - Mutarrif bin 'Abdullah (Sahih Muslim)
I went to Allah’s Apostle (ﷺ). The rest of the hadith is the same.
Grade: Sahih